2022
DOI: 10.3390/horticulturae8100959
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Harvest Date on Temporal Cannabinoid and Biomass Production in the Floral Hemp (Cannabis sativa L.) Cultivars BaOx and Cherry Wine

Abstract: The objectives of this study were to model the temporal accumulation of cannabidiol (CBD) and tetrahydrocannabinol (THC) in field-grown floral hemp in North Carolina and establish harvest timing recommendations to minimize non-compliant crop production. Field trials were conducted in 2020 and 2021 with BaOx and Cherry Wine cultivars. Harvest events started two weeks after floral initiation and occurred every two weeks for 12 weeks. Per-plant threshed biomass accumulation exhibited a linear plateau trend. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Similar results have also been documented in other studies where both CBD and THC concentrations increased gradually and then started declining at the end of the growing season (Latta & Eaton, 1975;Pacifico et al, 2008). Linder et al (2022a) also reported THC concentration increased gradually and then slightly decreased when the plant approached maturity. However, no such decrease in CBD concentration was observed in their study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results have also been documented in other studies where both CBD and THC concentrations increased gradually and then started declining at the end of the growing season (Latta & Eaton, 1975;Pacifico et al, 2008). Linder et al (2022a) also reported THC concentration increased gradually and then slightly decreased when the plant approached maturity. However, no such decrease in CBD concentration was observed in their study.…”
Section: Discussionsupporting
confidence: 90%
“…Linder et al. (2022a) also reported THC concentration increased gradually and then slightly decreased when the plant approached maturity. However, no such decrease in CBD concentration was observed in their study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As mentioned above, CBD concentration is primarily influenced by genetics and very little by environment (Burgel et al., 2020; Campbell et al., 2019; Toth et al., 2021). Other research further supports variation in CBD concentration due to cultivar (Linder et al., 2022a; Stack et al., 2021), as well as harvest timing (Burgel et al., 2020; Linder et al., 2022a; Yang et al., 2020).…”
Section: Introductionmentioning
confidence: 74%
“…Because CBD yield is a product of the biomass yield and CBD concentration, any factor affecting either or both of these parameters will affect CBD yield (Stack et al., 2021). Previous literature reports that the biomass yield of hemp is affected by plant maturity (Linder et al., 2022a), cultivar (Stack et al., 2021), transplanting date, and plant spacing (Linder et al., 2022b). As mentioned above, CBD concentration is primarily influenced by genetics and very little by environment (Burgel et al., 2020; Campbell et al., 2019; Toth et al., 2021).…”
Section: Introductionmentioning
confidence: 99%